Anti-TB Drug Side-Effects on the Treatment of Drug-Resistant Tuberculosis (DR-TB) in dr. Zainoel Abidin Hospital Banda Aceh - Arliny, Yunita; Muarif, Muhammad Fadjar; Mahdani, Wilda; Yanifitri, Dewi Behtri (Jurnal Respirologi Indonesia, 2025)
Background: Drug-resistant tuberculosis (DR-TB) is treated with second-line anti-tuberculosis (anti-TB) drugs which are comparatively less effective and more toxic. The increased toxicity of the drugs may lead to the occurrence of side effects throughout the treatment. The study aims to assess DR-TB patients' side effects and clinical profile at the dr. Zainoel Abidin Hospital, Banda Aceh. Methods: Observational descriptive study of DR-TB patients who underwent treatment from 2020 to 2022 at dr. Zainoel Abidin Hospital, Banda Aceh. The data was taken from medical records of patients which are then analysed using univariate analysis. Results: Out of 49 patients, most of them were male with 23 people (65,3%), belonging to the age group of 46-55 with 11 people (22,4%), worked as entrepreneurs with 11 people (22,4%), and most came from Banda Aceh and Aceh Besar with 14 people each (28,6%). Twenty-seven patients (65,1%) were suspected of secondary infection, most of which were cases of relapse from 10 people (20,4%). 39 of the patients (79,6%) had rifampicin-resistant tuberculosis. 36 patients (73,4%) were given individualized treatment with Lfx – Bdq – Lzd – Cfz – Cs being the most common drug combination given to 16 people (32.7%). All patients experienced side effects from the treatment, with the most common being nausea from 28 people (57,1%) followed by peripheral neuropathy from 19 people (38,8%). Conclusion: Side effects are commonly found in the treatment of DR-TB and may become more prevalent as the treatment continues. Educating the patient and treating side effects is important to maintain patient compliance.